Synthesis of nano-sized ceria (CeO2) particles via a cerium hydroxy carbonate precursor and the effect of reaction temperature on particle morphology - Majid Farahmandjou; Mahsa Zarinkamar (Journal of Ultrafine Grained and Nanostructured Materials, 2015)
Cerium oxide (CeO2) or ceria has been shown to be an interesting support material for noble metals in catalysts designed for emission control, mainly due to its oxygen storage capacity. Ceria nanoparticles were prepared by precipitation method. The precursor materials used in this research were cerium nitrate hexahydrate (as a basic material), potassium carbonate and potassium hydroxide (as precipitants). The morphological properties were characterized by high resolution transmission electron microscopy (HRTEM), scanning electron microscopy (SEM) and X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and UV-Vis spectrophotometer. XRD results showed face centered cubic CeO2 nanoparticles for annealed nanoparticles at 1000°C. SEM measurement showed that by increasing the calcinations temperature from 200 to 600°C, the crystallite size decreased from 90 to 28 nm. The SEM results showed that the size of the CeO2 nanoparticles decreased with increasing temperature. The particle size of CeO2 was around 25 nm as estimated by XRD technique and direct HRTEM observation. SEM and TEM studies showed that the morphology of the prepared powder was sphere-like with a narrow size distribution. The sharp peaks in FTIR spectrum determined the purity of CeO2 nanoparticles and absorbance peak of UV-Vis spectrum showed the small band gap energy of 3.26 ev.